The Protection Evaluation by The Grape-Seed-Loaded PVA/Chitosan Nanofiber Scaffolds on UV-Induced Skin Damage in Rabbits: Evaluasi Perlindungan oleh Kerangka Nanofiber PVA/Kitosan yang Diperkaya Biji Anggur terhadap Kerusakan Kulit Akibat Sinar UV pada Kelinci - Dina H. Sadiq; Majdy Faisal Majeed; Thaar R. Mhalhal; Prof. Dr. Ali Qassim Abdullah (Indonesian Journal on Health Science and Medicine, 2026)
General Background: Ultraviolet radiation is a major environmental factor causing oxidative stress, cellular damage, and structural deterioration in skin tissue. Specific Background: Recent advances in nanofiber technology have enabled the development of biomimetic scaffolds capable of delivering bioactive compounds for tissue repair and regeneration. Knowledge Gap: Limited experimental evidence exists on the combined use of PVA/chitosan nanofibers loaded with grape seed extract for restoring UV-damaged skin structure and antioxidant balance. Aims: This study aimed to evaluate the protective and therapeutic performance of grape-seed-loaded PVA/chitosan nanofiber scaffolds in a rabbit model exposed to chronic ultraviolet radiation. Results: The fabricated nanofibers demonstrated strong molecular interactions and uniform morphology, while biological evaluation showed that UV exposure induced severe oxidative, morphological, and histological damage. Treatment with the nanofiber scaffold for seven days led to restoration of skin architecture, reduction of inflammation and fibrosis, and significant improvement in antioxidant activity as confirmed by ABTS and DPPH assays. Novelty: This study demonstrates the successful integration of grape seed extract into nanofiber scaffolds with preserved structural integrity and functional bioactivity. Implications: The findings support the application of nanofiber-based systems as promising therapeutic platforms for skin regeneration and protection against ultraviolet-induced damage. KeywordsNanofiber Scaffold, Ultraviolet Radiation, Skin Damage, Grape Seed Extract, Antioxidant Activity Key Findings Highlights Uniform nanoscale fibers with stable molecular interactions achieved Severe tissue disruption observed after prolonged radiation exposure Short-term treatment restored structural organization and antioxidant balance